2015
DOI: 10.1186/s12889-015-1618-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations between e-cigarette access and smoking and drinking behaviours in teenagers

Abstract: BackgroundPublic health concerns regarding e-cigarettes and debate on appropriate regulatory responses are focusing on the need to prevent child access to these devices. However, little is currently known about the characteristics of those young people that are accessing e-cigarettes.MethodsUsing a cross-sectional survey of 14-17 year old school students in North West England (n = 16,193) we examined associations between e-cigarette access and demographics, conventional smoking behaviours, alcohol consumption,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(105 citation statements)
references
References 22 publications
(31 reference statements)
4
99
0
Order By: Relevance
“…The median number of participants was 3127 (IQR=1320 to 16 193). Participants’ ages were reported as: (A) middle and high school age,14 18 19 high school age only20; (B) aged 9–18+,17 10–16,33 11–18,15 12–18,29 13–18,32 ‘predominantly 14 to 15’,39 14–17,28 14–18,24 15,25 15–19,26 16–17,12 and 17–25 years37 ;and (C) a mean age (SD) of 12.2 (0.9) and 15.6 (1.2) for middle and high school students,31 14.0 (0.87) and 16.5 (0.77) for middle and high school students,22 12.4 (0.5),34 12.5 (0.6),27 14.5 (2.0),23 14.6 (0.7),40 14.6 (1.9),38 ∼14.7 (0.1),16 15.1 (2.1),41 16.2,36 and 16.4 (1.4) 11. All studies were funded by non-industry sources.…”
Section: Resultsmentioning
confidence: 99%
“…The median number of participants was 3127 (IQR=1320 to 16 193). Participants’ ages were reported as: (A) middle and high school age,14 18 19 high school age only20; (B) aged 9–18+,17 10–16,33 11–18,15 12–18,29 13–18,32 ‘predominantly 14 to 15’,39 14–17,28 14–18,24 15,25 15–19,26 16–17,12 and 17–25 years37 ;and (C) a mean age (SD) of 12.2 (0.9) and 15.6 (1.2) for middle and high school students,31 14.0 (0.87) and 16.5 (0.77) for middle and high school students,22 12.4 (0.5),34 12.5 (0.6),27 14.5 (2.0),23 14.6 (0.7),40 14.6 (1.9),38 ∼14.7 (0.1),16 15.1 (2.1),41 16.2,36 and 16.4 (1.4) 11. All studies were funded by non-industry sources.…”
Section: Resultsmentioning
confidence: 99%
“…Young VNP experimenters are more likely to engage in other risky behaviors (30, 53, 54) and have executive function deficits (55, 56) like those found in cigarette smokers (56, 57). These findings suggest a common liability model is more plausible than a gateway from VNP use to cigarette smoking (58, 59).…”
Section: Transitions From Never Smokermentioning
confidence: 97%
“…An earlier study conducted in Northwest England reported that the use of e-cigarettes in teenagers was associated with both heavy drinking and drinking to get drunk (Hughes et al 2015). Teenagers who use e-cigarettes may be more vulnerable to other forms of substance use and risk-taking behaviors.…”
Section: Discussionmentioning
confidence: 99%